1999
DOI: 10.1111/j.1572-0241.1999.872_a.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Plantago Ovata Seeds (Dietary Fiber) As Compared With Mesalamine in Maintaining Remission in Ulcerative Colitis

Abstract: Plantago ovata seeds (dietary fiber) might be as effective as mesalamine to maintain remission in ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0
12

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(136 citation statements)
references
References 28 publications
2
116
0
12
Order By: Relevance
“…It was demonstrated that colonic fermentation of Plantago ovata seeds yields butyrate, which serves as a nutrient for intestinal epithelial cells. The presence of butyrate in inflammatory bowel disease (IBD) in humans reduced the inflammation by inhibiting the production of cytokines and the activation of the transcription factor nuclear factor -kappa B (NF-κB) (Fernandez-Banares et al, 1999). In addition, butyrate protects the intestinal mucosa against injury and promotes mucosal healing (Scheppach et al, 1992).…”
mentioning
confidence: 99%
“…It was demonstrated that colonic fermentation of Plantago ovata seeds yields butyrate, which serves as a nutrient for intestinal epithelial cells. The presence of butyrate in inflammatory bowel disease (IBD) in humans reduced the inflammation by inhibiting the production of cytokines and the activation of the transcription factor nuclear factor -kappa B (NF-κB) (Fernandez-Banares et al, 1999). In addition, butyrate protects the intestinal mucosa against injury and promotes mucosal healing (Scheppach et al, 1992).…”
mentioning
confidence: 99%
“…The rate of relapse in patients with quiescent UC treated with soluble dietary fiber was not higher than that of patients given 5-ASA at the usual maintenance dose (5). Although the intake of dietary fiber, both soluble and insoluble, in the present UC patients was the same as that in the controls, the total fiber intake was less than that considered adequate for adult Japanese (29).…”
Section: Discussionmentioning
confidence: 55%
“…Soluble fibers are a different issue. There are studies suggesting that food products rich in soluble fibers, particularly germinated barley food stuff and seeds of the plantago ovata plant, might have positive effects in UC patients (20)(21)(22). It is known that short-chain fatty acids such as butyrate, which is a degradation product of soluble fibers, have positive effects on colonocytes.…”
Section: Resultsmentioning
confidence: 99%